Sampled-Data Control for Continuous-Time Singular Systems - El Aiss-Berazouq, H (Institute of Electrical and Electronics Engineers Inc., 2024)
This study focuses on addressing the sampleddata admissibility issue for a singular system. The primary objective is to develop a sampled-data controller that ensures the admissibility of such systems, utilizing an appropriate Lya-punov-Krasovskii Functional (LKF) to achieve less conservative outcomes. To achieve these goals, the system is first transformed into a time-delay system using the input delay approach. Subsequently, suitable admissibility criteria are formulated by introducing an appropriate LKF. To mitigate conservatism during the estimation of the LKF derivative, additional slack variables are introduced using the Finsler lemma. Finally, two numerical examples are provided to illustrate that the designed sampleddata controller effectively guarantees the admissibility of the considered systems. © 2024 IEEE.